2010
DOI: 10.1002/ejlt.201000059
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of extra‐virgin olive oil by spray‐drying: Influence of wall material and olive quality

Abstract: Encapsulation is a process by which small particles of core products are packaged within a wall material to form microcapsules. One common technique to produce encapsulated products is spray-drying which involves the conversion of liquid oils in the form of an emulsion into dry powders. Emulsification conditions, wall components, and spray-drying parameters have been optimized for the microencapsulation of different extra-virgin olive oils. To achieve this goal, the influences of emulsion conditions have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 23 publications
(26 reference statements)
8
65
2
5
Order By: Relevance
“…Furthermore, the monosaturated fatty acids (SFAs) were more stable during the spray-drying process as comparison with PUFAs. Similar results were reported by Calvo et al (2010), who found that, the fatty acid profile of olive oil was unaltered during the microencapsulation process. After the accelerated oxidation experiments, the contents of saturated and monosaturated fatty acids increased, whereas the content of PUFAs decreased.…”
Section: Fatty Acid Analysissupporting
confidence: 90%
“…Furthermore, the monosaturated fatty acids (SFAs) were more stable during the spray-drying process as comparison with PUFAs. Similar results were reported by Calvo et al (2010), who found that, the fatty acid profile of olive oil was unaltered during the microencapsulation process. After the accelerated oxidation experiments, the contents of saturated and monosaturated fatty acids increased, whereas the content of PUFAs decreased.…”
Section: Fatty Acid Analysissupporting
confidence: 90%
“…Formulasi mikroenkapsulat pepton dilakukan dengan mengacu pada metode Calvo et al (2010) pepton cair dan bahan penyalut maltodekstrin dicampurkan dengan perbandingan 1:3. Maltodekstrin dengan konsentrasi 1%, 2%, 3% dihomogenisasi dengan pepton cair menggunakan homogenizer dengan kecepatan 22.000 rpm dengan waktu 5 menit, 10 menit, dan 15 menit.…”
Section: Formulasi Dan Pembuatan Mikroenkapsulat Peptonunclassified
“…Moreover, not all encapsulating agents are meet all the properties needed, so the modified encapsulating agents by combination with other coating materials such as oxygen scavengers, antioxidants, chelating agents and surfactant are required. 16 The most popular encapsulation agents used in microencapsulation by spray drying are gum arabic, maltodextrin and chitosan. This is due to a high encapsulation efficiency of some oils extracted (53%).…”
Section: Encapsulation Materialsmentioning
confidence: 99%